Factors that generate pleasure/suffering at work, impacting the mental health of nursing professionals (Research, Society and Development, 2025)
Objective: Highlight the relationships of pleasure/suffering and their communication with the work activity of nursing professionals. Method: Cross-sectional, descriptive study, with a qualitative design of the content analysis type. Nurses, Nursing Technicians and Nursing Assistants from the Nursing Department of the Hospital de Clínicas de Porto Alegre were interviewed, who were removed from work due to a psychological illness in the period from 2019 to 2021. It’s been used the software Nvivo for categorization and the Laurence Bardin’s Content Analysis Techniques to verify the data. Results: Based on the analysis, the sources of pleasure identified were appreciation for nursing work and recognition of the work performed, while the sources of suffering were the COVID-19 pandemic and work organization. Finally, interpersonal relationships were considered sources of pleasure for some and suffering for others. Conclusion: For all interviewees, the pleasure/suffering relationship is established within the workplace, ultimately leading to mental health damage and psychosomatization. This relationship ultimately demonstrates that the care provided by healthcare professionals is directly linked to the mental state of the workers who provide it.